Evaluating the Spatial Distribution of The Green Area in Diwaniyah City by using geographic information systems (Case study: The Second District) (Journal of Planner and Development, 2018)
the success of any city and integration of function in fulfilling its various functions which primarily depend on the efficiency of the Spatial Distribution of The Green Area. By the efficiency of the Spatial Distribution of The Green Area will send the service for all people that lived in the city. Cities in the developed countries had long realized the crucial importance of parks as a major arenue for relaxation , education , and entertainment ; in addition to their benefits as Environmentally. The all Kinds of green area should be placed among the primary goals of city planning and a major coneern in urban design . The Green Area are also a primary tool for the beautification of city landscape, And so the research has focused on describing the existing of the Spatial Distribution Of The Green Area in the study area (The Second District) , and efficiency of its by use the standards urban planning, standars ( area & accessibility ),evaluation the efficiency from knowing the density and problems as existing , and analyized the service of the grean area in the Diwaniyah city . Therefore this research goes to describe and analyze the Spatial Distribution Of The Green Area in the study area (The Second District) Which is represent by the green area where the planning and the completion , based on the field study for the Second District(quarter district )grade ,The study took two lines: First: concern with study existing the Spatial Distribution of the Green Area including the all kind of green area where the planning and the completion. and service is represented by analysis of the results of the field study of the green area in study area that present by the efficiency the existing of the Spatial Distribution Of The Green Area by using standards of the urban planning( area standard & accessibility standard) , and analyized the service zone for the green area planning and completion , so the analysis of the practical have percent of areas of the green area which the planning and the completionand the area must require, and percent of the service compact zone based up on the accessibility standard for the levels ( nieybourhood ,quarter , district ). So based upon the extracted Indicators from Evaluating the Efficiency of the Spatial Distribution of The Green Area by using the geographic information system (GIS) and using the standards that previous defined, there are the Efficiency of the Spatial Distribution of The Green Area aren’t Efficiency and needed to replanning The study ends up by stating the desired strategies for the urban Planning processes the Efficiency Spatial Distribution of The Green Area for increasing the Efficiency of service of the green area in Diwaniyah City, for spetialy study area (The Second District)